ANALISIS BIAYA PRODUKSI BERAS DAN PENDAPATAN PADA UD. REZEKI INDAH - Nurdianti, Pipi; Sabarudin, Sabarudin; Bustang, Bustang (Komunitas Manajemen Kompetitif, 2025)
This study aims to analyze the cost of rice production and income at UD. Rezeki Indah. The formulation of the problem in this study is: (1) How are the production costs at UD. Rezeki Indah? and (2) How is the income at UD. Rezeki Indah? The research method used is a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the production costs at UD. Rezeki Indah consist of several main components, namely raw material costs, labor costs, and overhead costs. The largest production costs come from raw material costs, which contribute around 43.41% of the total production costs. The total production costs incurred by UD. Rezeki Indah in periods I and II were Rp. 640,600,000,-. Income is obtained from the sale of products with an average volume of 880 sacks during a year, the selling price per sack is Rp. 700,000, -. And there is additional income due to the sale of seeds of Rp. 25,000,000 from From the analysis conducted, So the total income per year is Rp. 641,000,000, -. Based on these findings, it can be concluded that UD. Rezeki Indah has a less than good income. Keywords: Raw Material Cost, labor costs, overhead costs, Income